Studies on Characteristics of Rain Fade at 23 GHz for Terresterial Links - Sum, Chin Sean; Din, Jafri; Tharek, A. R.; Abidin, M. Z. (2003)
-Terrestrial links operating at frequencies higher than IO GHz suffers degradation due to rain. Various researches have been conducted to study rain-induced degradations such as rain attenuation. Apart from rain attenuation, rain fade is also a major factor affecting the performance of a terrestrial microwave link. This paper therefore, seeks to investigate the impacts of rain fade to the performance of terrestrial microwave links. In this paper, rain fade slope and rain fade depth are investigated and analyzed. The superposition of rain attenuation and rain fade is also investigated. Signal fall time and recovery time are also major concern n this paper. All the analysis leads to understanding on the impacts of rain fade on the performance and reliability of microwave terrestrial links.